A dynamic interactive protocol for distributed multimedia over ATM networks. - Ghinea, Gheorghita. (My University, 1996)
This report describes a dynamic Quality of Service (QoS) - based call admission protocol tor distributed multimedia over ATM networks. The protocol incorporates the innovative idea of an extended QoS. This is a composite term which takes account of not only classic QoS multimedia measures, but also of the human aspect of the interaction through human receptivity. For this scenario, different QoS negotiation strategies have been formulated and then simulated with a view towards the establishment of a protocol knowledge base. Separately, a session pricing policy has been elaborated and its effect on user behaviour and network resource allocation studied.
A research report subuutted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science. Degree awarded with distinction
Keywords: Interactive multimedia.; Asynchronous transfer mode.